Impact of water deficiency on cotton ginning efficiency, fiber quality, and seed composition - Bai, Fang; Donohoe, Sean P.; Abdelraheem, Abdelraheem; Bellaloui, Nacer; Mubvumba, Partson; Zeng, Linghe (Frontiers in Plant Science, 2026)
Water deficiency is a prevalent abiotic stress that significantly constrains cotton productivity worldwide. This study aimed to evaluate the impact of water deficiency on ginning efficiency, fiber quality, and seed composition in cotton (Gossypium spp.). Ten cotton genotypes were assessed under irrigated and non-irrigated field conditions. Water deficiency markedly reduced plant height and the number of bolls, with genotypes MD 52ne, MD 25-26ne, and 1517–99 displaying high sensitivity, whereas CIM 432 exhibited notable water deficiency tolerance. Ginning efficiency analysis showed a general reduction in energy requirements under water deficiency, particularly in MD10-5, MD 15, and MD 52ne. CIM 432, however, maintained high boll numbers, and stable ginning rate and ginning energy under stress. Fiber quality traits such as length, strength, and uniformity were adversely affected by water deficiency across most genotypes, although CIM 432, MD 15 and 84524 showed greater stability. Correlation analyses under water deficiency revealed strong positive associations among fiber length, strength, and uniformity, along with a significant negative correlation between lint percentage and oil content, suggesting a trade-off between lint yield and seed oil accumulation. Cottonseed composition analysis indicated that when oil content declined under water deficiency, protein and seed fiber levels remained relatively unaffected. Significant genotypic variation was observed for most traits, with minimal genotype-by-treatment interactions, indicating consistent genotype performance across irrigated and non-irrigated treatments. Overall, CIM 432 emerged as a robust candidate for breeding water deficiency-tolerant cotton, combining agronomic resilience with stable fiber quality. These findings underscore the complexity of genotype-water deficiency stress interactions and highlight the importance of integrated phenotypic assessment for developing water deficiency-tolerant cotton varieties.